UPAYA MASYARAKAT DALAM MENGATASI BENCANA BANJIR BANDANG DI KELURAHAN LAMBUNG BUKIT KECAMATAN PAUH KOTA PADANG - Reny, Afrilla; Juita, Erna; Zuriyani, Elvi (Pendidikan Geografi, 2013)
Watershed management, especially in Pauh seem less good. This can be seen by the occurrence of flood disasters in the Bukit Pauh subdistrict. Kuranji upstream watershed damage caused by human activities, such as indiscriminate logging, land conversion along the watershed and land use change upstream. This shows that people do not understand how to better manage watersheds, people prefer utilizing watershed areas as a source of economicThis study aimed to obtain information, analyze and discuss data on the communitys efforts to overcome flash floods in Hull Village Bukit Padang Pauh subdistrict which includes: 1 ) conservation efforts in the watershed and 2 ) land use throughout the watershed . This research is descriptive . Population in this research is that there are people in flood -prone areas in the Village Gastric Bukit Padang Pauh subdistrict consists of 4 RT 13 RW and 814 families numbering . Samples were taken in 2 ways , first ; samples taken territory with purposive sampling techniques , namely the selection of areas affected by flash floods in Hull Village Bukit Padang Pauh subdistrict namely RW III on RT 1 and 4 and the second, the sample of respondents is taken with total sampling , so that the sample in this study amounted to 113 families ( KK ) . The research found that : 1 ) The efforts of the community , among others, is to understand the benefits that society Batang Kuranji periodically clean the area around the watershed , not cutting trees , do not engage in activities that goes contrary to the watershed , participate and perform watershed by utilizing land DAS 50-100 m from the edge of the river and 2 ) efforts to regulate land use throughout the watershed in the Village District Gastric Bukit Padang Pauh quite well with the level of achievement of respondents 61,1 %